Respuesta :

To simplify the expression you can first use this property of exponents

[tex](a\cdot b)^m=a^mb^m[/tex]

Then you have

[tex]\begin{gathered} (x^3y^5)^3=(x^3)^3(y^5)^3 \\ (x^3y^5)^3=x^{3\cdot3}y^{5\cdot3} \\ (x^3y^5)^3=x^9y^{15} \end{gathered}[/tex]

Now apply this property of exponents

[tex]a^b\cdot a^c=a^{b+c}[/tex]

Therefore, you have

[tex]\begin{gathered} (x^3y^5)^3\cdot-x^6y^5=x^9y^{15}\cdot-x^6y^5 \\ (x^3y^5)^3\cdot-x^6y^5=x^9\cdot-x^6\cdot y^{15}\cdot y^5 \\ (x^3y^5)^3\cdot-x^6y^5=-x^{9+6}\cdot y^{15+5} \\ (x^3y^5)^3\cdot-x^6y^5=-x^{15}\cdot y^{20} \\ (x^3y^5)^3\cdot-x^6y^5=-x^{15}y^{20} \end{gathered}[/tex]